Influence of the development of learning objectives and performance indicators in the competence of the students of 8th year EGB C of Unidad Educativa Pasionista in the first five- months term in the school year 2013-2014. Design of an evaluation instrument to asses learning outcomes of 8th year EGB. - Valencia Robles, Jeannette De Fátima (2014)
This research was carried out because of the need of more specific objectives to develop the four language skills of 8th graders. The study explored how the development of specific learning objectives and performance indicators may influence the competence of 8th Year EGB C students in Unidad Educativa Pasionista during the first five-month period of the 2013-2014 School Year. The investigation aimed to develop specific learning objectives based on a comparative study, develop performance indicators, categorize students’ competence, and design an evaluation instrument. The research followed a qualitative method to approach this case study in its three stages: the comparative study between the objectives and indicators of the curriculum and the textbook was done; the previous information contributed to the development of the specific learning objectives and performance indicators; seven instruments of evaluation were elaborated to assess participants’ performance. It was found that being aware of what the learning objectives are and how the appropriate performance looks like, promote a more meaningful teaching practice and learning experience. This case study also presents the basis for further applications on this topic.